Inovasi Alat Pengemasan Tempe dalam Meningkatkan Produktivitas dengan Pendekatan Antropometri dan Penilaian Biaya - Prima, Sabrian; Murnawan, Hery (Fakultas Teknik Universitas Tulang Bawang, 2025)
Tempeh, a soybean-based product fermented by the fungus Rhizopus oligosporus, is a traditional Indonesian food known for its high nutritional value, particularly as a source of plant-based protein. The Tempeh Production House